STRATEGI MANAJEMEN DAN SISTEM PENGENDALIAN MANAJEMEN DALAM MENCIPTAKAN KEUNGGULAN BERSAING - HANANTIJO, GM. DJOKO (Universitas Surakarta, 2012)
The development of economics and information technology Â spur on increasing competition, therefore the corporation management must seek and apply business strategy. This is done to make the corporation win the competition and superior to compete with its competitors. One of the concepts that can be applied is management accounting strategy and management controlling system that can help simultaneously to face business competition. In management strategy, there are many supporting elements to support management strategy to win competitive superiority, such as accounting system frame, the three concepts (product life cycle, experience curve, the growth of market share), and the main contribution in management strategy. The threatÂ and opportunity caused by competition, based on research analysis says that controlling management process can be used to manage the strategy appearance to face threat and create opportunity. Theoritically, it shows dynamic relationship between management strategy and controlling management system that can help corporation to face competition and competitive superiority. Keywords:Â product life cycle, Boston Consulting Group.